Bioavailability of contaminants in urban soils - Attanayake, Chammi (Kansas State University, 2014)
Urban soils may contain harmful levels of potentially toxic contaminants. These contaminants transfer to humans via two exposure pathways: direct transfer (soil-humans by soil ingestion, dermal exposure and inhalation) and food chain transfer (soil-plant-humans). Soil amendments alter the speciation of the contaminants in soils and thereby modify their bioavailability. The objectives of this research were to access the plant availability of lead (Pb), arsenic (As), and polycyclic aromatic hydrocarbons (PAHs); bioaccessibility and speciation of soil Pb, and As; and dermal absorption of soil PAHs in contaminated urban soils; and effectiveness of soil organic amendments on reducing contaminant bioavailability. Two field experiments were conducted in Kansas City, MO and Indianapolis, IN. Both sites had elevated concentrations of Pb in soils (Kansas City site: 30-380 mg kg⁻¹ and Indianapolis site: 200-700 mg kg⁻¹) . Indianapolis site’s soils also had elevated concentrations of As (40-100 mg kg⁻¹) and PAHs (benzo[a]pyrene: 1-10 mg kg⁻¹) . A control treatment (no-compost) and compost-types (leaf compost and/or composted biosolids, non-composted biosolids, mushroom compost) were used as treatments. A leafy vegetable, a fruiting vegetable and a root crop were grown for two growing seasons. The treatments were arranged in split-plot design (main plot factor: compost; sub-plot factor plant-type). An in vitro steady fluid experiment was conducted using human skins to examine the dermal transfer of soil PAHs. The concentrations of Pb, As, and PAHs in the vegetables were low, except Pb in root crops. Compost reduced the bioaccessibility of Pb, but did not change the bioaccessibility of As. Selected soil samples were analyzed for speciation of Pb using extended x-ray absorption fine structure spectroscopy. The predominant Pb species were Pb sorbed to Fe oxy(hydr)oxide and to organic C. Stable Pb phosphates (pyromorphite) was formed during the in vitro extraction. Dermal transfer experiments showed PAHs in the contaminated soils did not transfer through the skin. Stratum conium of the skin acted as a barrier for dermal transfer of soil PAHs. In general, the risk of food chain transfer of soil Pb, As, and PAHs were low in the studied sites and can be further reduced by compost addition. Bioaccessibility of Pb and As in urban soils were low. Dermal absorption of soil PAHs was insignificant.
Keywords: Urban soils; Lead; Arsenic; Polycyclic aromatic hydrocarbons; Environmental Sciences (0768); Soil Sciences (0481)